John Dahl and Neo-Noir: Examining Auteurism and Genre - Monaco, Paul (Lexington Books, 2010)
In John Dahl and Neo-Noir: Examining Auteurism and Genre, Paul Monaco provides a focused inquiry into the first three feature films that director John Dahl made for theatrical release: Kill Me Again (1989), Red Rock West (1993), and The Last Seduction (1994). Subsequent to their releases, these three films became identified in academic film criticism as neo-noir, and Dahl was labeled a 'noir-meister' who made 'a cottage industry of neo-noir.' The importance of these three films, and Monaco's investigation of them, is how they illuminate a modern director's creative process in relation to an emerging genre. Dahl is rightly recognized for his directorial vision and his creative style. His approach to film direction, and his distinctiveness of vision, is thoroughly explored in the book. Using interviews with the professionals with whom Dahl has worked closely, Monaco also explores basic notions about auteurism and how genre is defined. Considering Dahl's extensive directing for television alongside his first three films, John Dahl and Neo-Noir ultimately demonstrates how this groundbreaking director is a prime example of a modern 'director for hire.'